Risk Factors and Short-Term Outcome of Birth Asphyxiated Babies in Dhaka Medical College Hospital (Bangladesh Journal of Child Health, 2010)
Background: Perinatal asphyxia is the most important preventable cause of cerebralinjury in the neonatal period leading to very high neonatal mortality and morbidity indeveloping countries. Little can be done for a baby affected by severe perinatalasphyxia. So, prevention is unquestionably desired.Objective: To identify the maternal and fetal risk factors for the development of birthasphyxiated babies and to see the short term outcome of the affected babies.Methods: An analytical type of or observational study was done in the Special CareBaby Unit (SCBU) of Dhaka Medical College Hospital from October 2003 to March2004. Identification of the risk factors was done by retrospective comparison of thecases and controls. Outcome was analyzed by cross sectional comparative study.One hundred consecutive cases of birth asphyxia, admitted in SCBU, were enrolledin the study. Another 30 neonates admitted during this period for other reasons (i.e.,jaundice, septicemia, low birth weight) were taken as control. Necessary informationwere collected by detailed history taking, clinical examination and close follow up ofthe hospital course, using pre-designed questionnaire and recording form.Results: Male: female ratio 3:2 both in the cases and controls. Mean age on admissionwas 13.8 hours and 2.6 days for case and control respectively. Identified importantmaternal risk factors were primiparity (57% in cases vs. 33.3% in control), hypertension(16.6% vs. 3.3%), pre-eclamptic toxemia of pregnancy (24% vs. 13.3%), prolongedrupture of membrane (33.3% vs. 6.7%), prolonged labour (34% vs. 3.3%) and useof oxytocin during labour (16% vs. none). All these were statistically significant (p